Change in adiposity is associated with change in glycoprotein acetyls but not hsCRP in adolescents with severe obesity - Mansell Toby; Bekkering Siroon; Longmore Danielle; Magnussen Costan G; Vlahos Amanda; Harcourt Brooke E; McCallum Zoe; Kao Kung-Ting; Sabin Matthew A; Juonala Markus; Saffery Richard; Burgner David P; et al. (Elsevier, 2025)
Background
Obesity-associated chronic inflammation mediates the development of adverse cardiometabolic outcomes. There are sparse data on associations between severe obesity and inflammatory biomarkers in adolescence; most are cross-sectional and limited to acute phase reactants. Here, we investigate associations between adiposity measures and inflammatory biomarkers in children and adolescents with severe obesity both cross-sectionally and longitudinally.
Methods
From the Childhood Overweight Biorepository of Australia (COBRA) study, a total of n = 262 participants, mean age 11.5 years (SD 3.5) with obesity had measures of adiposity (body mass index, BMI; % above the 95th BMI-centile, %>95th BMI-centile; waist circumference, WC; waist/height ratio, WtH; % total body fat, %BF; % truncal body fat, %TF) and inflammation biomarkers (glycoprotein acetyls, GlycA; high-sensitivity C-Reactive Protein, hsCRP; white blood cell count, WBC; and neutrophil/lymphocyte ratio, NLR) assessed at baseline. Ninety-eight individuals at mean age of 15.9 years (3.7) participated in a follow-up study 5.6 (2.1) years later. Sixty-two individuals had longitudinal data. Linear regression models, adjusted for age and sex for cross-sectional analyses were applied. To estimate longitudinal associations between change in adiposity measures with inflammation biomarkers, models were adjusted for baseline measures of adiposity and inflammation.
Results
All adiposity measures were cross-sectionally associated with GlycA, hsCRP and WBC at both time points. Change in BMI, %>95th BMI-centile, WC, WtH and %TF were associated with concomitant change in GlycA and WBC, but not in hsCRP and NLR.
Conclusion
GlycA and WBC but not hsCRP and NLR may be useful in assessing adiposity-related severity of chronic inflammation over time.